Hubungan Motivasi dan Minat Belajar Terhadap Pencapaian Kompetensi Pada Mahasiswa Keperawatan Semester Enam Di Akademi Keperawatan Wirahusada Medan - Tetty Suriany Limbong (JUKEJ : Jurnal Kesehatan Jompa, 2023)
The principal issue in this research are many factors that affect the achievement of clinical competencies of nursery practice that includes the students’ motivation and interest factors. Student willingness to participate in clinical practice as a nurse nursery is a professional motivational and has a good competence so that they can compete in the world of work. The practice of nursery clinic is a place to learn before entering into the world work. This research aims to find out the relationship of interest and learning motivation with achievement of target competencies of nursery practice clinic VI semester students study program Nursery Wirahusada Medan academic year 2022.This research is a cross sectional correlational approach. Entire student population is Academic Nursery Wirahusada Medan the academic year 2022 amounted to 54 people, with total sampling. The independent variables of motivation and learning interest. Dependent variable was the achievement of clinical competencies of nursery practice. Measurement of variables using questionnaires and observation sheets, and then analyzed using multiple linear regression method.Based the results of statistical tests to obtain the R square of 0.221, at variablemotivation in getting value p = 0.043 while in the learning interest variables obtained P value = 0.002. Regression coefficient shown in the motivation 1.571 and 95% CI = 1.063<PR,2.322 and value PR interest 1.925 and 95% CI = 1.266. PR.2.927. This research concludes that the motivation and interest have a significant relationship with achievement of target competencies of nursery practice clinic.